Sinners? Scroungers? Saints? unmarried motherhood in twentieth-century England - Thane, Pat 1942-; Evans, Tanya 1972- (Oxford University Press, 2012)
A detailed exploration of the real lives of unmarried mothers in England through the past century, this book argues that the 'permissive' sixties were largely a revolt against the secrecy and hypocrisy that went before